Non-operative treatment for bowel obstruction in a 37-year-old woman with common mesentery: a case report - Manuela Mastronardi; Biagio Casagranda; Nicolò de Manzini; Silvia Palmisano (Emergency Care Journal)
Common mesentery is a rare congenital anomaly caused by abnormal rotation of the omphalomesenteric loop during embryonic development. We report the case of a 37-year-old woman who presented with lower abdominal pain and fever. Physical examination revealed localized tenderness, and laboratory tests showed elevated inflammatory markers. Computed tomography revealed common mesentery with small bowel obstruction, and abnormal cecal positioning. There were no signs of ischemia or perforation. Conservative treatment was initiated, including nasogastric decompression, Gastrografin challenge, intravenous fluids, analgesics, and antiemetics. The patient improved clinically, tolerated refeeding, and was discharged on day five. At three-month follow-up, she remained asymptomatic. Magnetic resonance imaging confirmed the congenital anomaly and excluded other pathological findings. This case demonstrates that non-operative management may be an effective option in stable adult patients with bowel obstruction due to common mesentery.